Investing the Aesthetics of Gulāb Bāgh Gateway: A Diminishing Mughal Monument (Al-Qamar, 2025)
The city of Lahore has been controlled by several dynasties throughout course of its history but it reaches its apogee of its splendor under the Mughal Empire between the late 16th and early 18th century and served as its capital city for many years. The Mughals were endowed with remarkably taste for constructing magnificent structures. Gulābi Bāgh gateway is one of those monumental structures, built during Mughal Empire. On the facade of Gulābi Bāgh gateway, there are inscriptions in Persian language which have symbolical connotations. The structure is embellished with frescos painting. The internal worn-out walls are decorated with lotus flowers and cypress tree which also have symbolical representations. There is no doubt that Architectural structures are helpful to understand the chronological notions about the situation of city especially gateways which are erected for so many reasons. This paper is an effort to interpret the meanings from the symbolic inscriptions and embellishments carved on the walls of the magnificent piece of art and architecture i.e Gulabi Bagh. In contemporary period the Mughal architecture is one of those remaining structures which are considered as a heritage of Pakistan. This research also highlights the fact that such buildings are ruined by public who torn up their history by the ancestries and are not even conscious of the loss.
Keywords: Gulābi Bāgh gateway; Mughal Architecture; Monument; Inscriptions; Heritage